2021
DOI: 10.1590/pboci.2021.069
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Colloidal Selenium Nanoparticles in Chitosan Solution against Streptococcus mutans, Lactobacillus acidophilus, and Candida albicans

Abstract: Objective: To investigate the antimicrobial activity of colloidal selenium nanoparticles in chitosan solution (Cts-Se-NPs) against Streptococcus mutans, Lactobacillus acidophilus, and Candida albicans. Material and Methods: Cts-Se-NPs solution was prepared using a simple chemical reduction method. The MIC and MBC against S. mutans, L. acidophilus, and C. albicans were determined using the broth dilution assay. Results: The Cts-Se-NPs had remarkable antimicrobial activity against S. mutans, L. acidophilus, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The toxicity of SeNPs was assessed in various cell lines, revealing minimal or negligible toxicity towards normal cells, even at the same concentration range used for antimicrobial testing. Remarkably, SeNPs exhibited a robust antiproliferative effect on cancer cells [ 50 ]. The anticancer activity of SeNPs can be explained by their pro-oxidant property.…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity of SeNPs was assessed in various cell lines, revealing minimal or negligible toxicity towards normal cells, even at the same concentration range used for antimicrobial testing. Remarkably, SeNPs exhibited a robust antiproliferative effect on cancer cells [ 50 ]. The anticancer activity of SeNPs can be explained by their pro-oxidant property.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this classification denotes that the S. mutans bacterial strain has the potential to operate as a moderate biofilm producer [27]. Several studies have previously reported on the MIC of SeNPs, which have concluded that the MIC against S. mutans could be as low as 68 µg/mL [41]. While these studies have reported commendable results at relatively low concentrations, MICs are only a representation of the activity of a drug against bacteria.…”
Section: Effect Of Size and Concentration On Antibiofilm Activity Of ...mentioning
confidence: 99%
“…Denture use may change the oral environment and provide a suitable condition for the proliferation and colonization of microorganisms [1,2]. For example, C. albicans, as a commensal fungus that colonizes the human mucosal surfaces in the oral cavity, is present in 30-60% of healthy individuals and 60-100% of denture wearers [3].…”
Section: Introductionmentioning
confidence: 99%